Experimental Evaluation of Thermal Energy Storage (TES) with Phase Change Materials (PCM) for Ceiling Tile Applications. Issue 1 (15th December 2020) - Velasco-Carrasco, Mariana; Chen, Ziwei; Aguilar-Santana, Jorge Luis; Riffat, Saffa
Thermal energy storage systems (TES) are an effective technology to improve the energy efficiency while reducing the energy consumption in buildings. The integration of phase change materials (PCMs) as latent thermal energy is a popular method to incorporate them into the building envelope, reducing the energy demand and helping maintain the thermal comfort. In this experimental evaluation, the application of S23 ceiling panels to enhance the building performance is investigated. To analyse the PCM panels, a test room was artificially heated securing the melting temperature for the material; the results show that the S23 panels were able to absorb and increase the room temperature by 5 °C. During the cooling period, the PCM ceiling tiles help maintain higher room temperatures, up to +1.5 °C. The S23 panel temperature was able to drop below its melting point after 6 hours of cooling, demonstrating its capacity to complete the thermal cycle. The panel thermal conductivity range was found between 0.19–0.24 W/(m·K). It can be concluded that the addition of the S23 ceiling panels can be considered as an innovative solution for the application of passive TES in building envelopes, leading to energy savings by absorbing, storing and helping maintaining the ambient room temperature, therefore reducing the requirement for artificial heating and cooling.